2011
DOI: 10.1097/mph.0b013e31820db7b1
|View full text |Cite
|
Sign up to set email alerts
|

Asthma is a Distinct Comorbid Condition in Children With Sickle Cell Anemia With Elevated Total and Allergen-specific IgE Levels

Abstract: Asthma in children with sickle cell anemia (SCA) is associated with increased morbidity and mortality. However, the definition of asthma in SCA is based on a physician's impression. In a retrospective cohort of children with SCA, relationships between a physician diagnosis of asthma and total and allergen specific IgE levels were evaluated. In children with SCA, elevated total and specific IgE levels were significantly associated with a diagnosis of asthma (P<0.05), further supporting the concept that asthma i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…For example, total IgE is increased in chi-SCD mice compared with chi-HbA mice whether or not the mice are sensitized to OVA. This is similar to reports in humans, where IgE is increased in individuals with SCD (with or without asthma) compared with the general population (20,21). IgE production is stimulated by IL-13 (22).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…For example, total IgE is increased in chi-SCD mice compared with chi-HbA mice whether or not the mice are sensitized to OVA. This is similar to reports in humans, where IgE is increased in individuals with SCD (with or without asthma) compared with the general population (20,21). IgE production is stimulated by IL-13 (22).…”
Section: Discussionsupporting
confidence: 78%
“…In sensitized mice, total IgE in the OVA-Sen chi-SCD mice was further increased compared with OVA-Sen chi-HbA mice ( Figure 3). These data suggest that SCD specifically contributes to total circulating IgE levels at baseline or after OVA sensitization, similar to humans with SCD (20,21).…”
Section: Total Ige Levelsmentioning
confidence: 70%
“…Respiratory morbidity, including asthma2 3 and acute chest syndrome (ACS),4–6 is common in children with SCD. Elevated total IgE in SCD is associated with increased wheeze and cough and is an independent risk factor for ACS 7.…”
Section: Introductionmentioning
confidence: 99%
“…Airway hyper-responsiveness (AHR) measured using cold air or exercise has been reported in 20–64% in children with SCD3 8 9 but is not associated with symptoms of reactive airway disease8 or ACS 9. AHR to methacholine is no more frequent in SCD children reporting asthma symptoms than unselected SCD children,10 11 suggesting that AHR may be a component of SCD8 while asthma may represent a distinct coexisting condition 2. Ethnicity may be an important factor though, since AHR has been reported in 42% of young, healthy, African-American children, despite a doctor diagnosis of asthma in only 10% 12.…”
Section: Introductionmentioning
confidence: 99%
“…Studies looking at whether IgE levels can be used to discriminate between those with and without asthma have been inconsistent. While some studies have demonstrated that children and adults with SCD and asthma have higher IgE levels than those without asthma, [21, 42, 43] Strunk et al found that there was no difference in IgE levels between those with and without a physician diagnosis of asthma among children in the SAC cohort [3]. Having ≥ 2 positive skin tests to aeroallergens was more common among those with asthma compared to those without asthma in the SAC cohort, but skin test reactivity did not add much to a predictive model for discriminating “asthma” from “no asthma” in this cohort [3].…”
Section: Introductionmentioning
confidence: 99%